Stand structure in terrestrial ecosystems - Davis, F. W.; Roberts, D. (Methods in Ecosystem Science, 2000)
This chapter provides a brief overview of instrumentation and methods for characterizing vegetation structure at the stand level, where a stand is defined as an area of relatively uniform physical environmental conditions, vegetation structure and plant community composition (Barbour et al. 1987). By vegetation structure we mean the 3-dimensional distribution of above-ground phytomass integrated over some period of time. We will not consider the temporal components of stand structure such as diurnal variation in leaf orientation or seasonal phenology, focusing instead on methods for estimating structural variables at a particular point in time.